Implementation of effective time management technologies in the managerial activities of a modern enterprise - Dan, Li (Харківський національний автомобільно-дорожній університет, 2025)
The object of research is the processes of time management at a modern enterprise. The subject of the study is the methods and tools of time management that are used to increase the efficiency of the enterprise. The purpose of the study is to analyze the features of the implementation of time management at a modern enterprise and develop recommendations for improving time management to increase the productivity and efficiency of the enterprise. Research methods include logical analysis, direct calculations, expert questioning, and modeling of time management processes.
Keywords: effective time management technologies; managerial activities; management; time management; managerial activity of the enterprise